Penentuan Order Quantity Bahan Baku Pupuk Bersubsidi Jenis NPK Menggunakan Metode EOQ di PT. XYZ - Kurniawan, Adji Candra; Febrianti, Risa (Institut Teknologi Adhi Tama Surabaya, 2023)
Fertilizer has an important role in supporting the productivity of food crops. The Indonesian government provides subsidized fertilizers in an effort to support the fulfillment of national food needs. The number of subsidized fertilizer needs targeted by the government increases every year. Therefore, appropriate inventory planning is needed to realize the subsidized fertilizer production target that has been set by the government. The type of NPK fertilizer is one of the concerns because this type of subsidized fertilizer has a high demand rate, but its production figure is still far from the realization target. So that in this study the author aims to conduct a comparative analysis of inventory with the policies set by the company, namely Minimum-maximum with the Economic Order Quantity (EOQ) method. The EOQ method considers several costs, such as holding costs, raw material prices, and ordering costs. There are several outputs produced by the authors in this study, such as the frequency of orders, safety stock, reorder points, and total inventory costs. With this policy, the total cost of raw material inventory that must be spent for the manufacture of NPK fertilizer is Rp 4,257,606,170. And by using the EOQ method, it can save the company's total inventory cost of Rp. 121,368,688 or 2.77%.